Mosquito-transmitted Highlands J virus in Florida - C. Roxanne Rutledge-Connelly (EDIS, 2004)
Highlands J virus (HJ) is a mosquito-transmitted alphavirus that is similar to eastern equine encephalitis virus (EEE) in its natural cycle; it is transmitted from Culiseta melanura mosquitoes to songbirds in freshwater swamps. It has a low pathogenicity in mammals and is rarely seen in humans or horses. There have been outbreaks reported in penned birds but the symptoms are mild compared to EEE. This document is Fact Sheet ENY-720, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Serivce, Institute of Food and Agricultural Sciences, University of Florida. Date first published: October 2004.